Probable Drug Interaction Between Etanercept and Cyclosporine Resulting in Clinically Unexpected Low Trough Concentrations: First Case Report - Wen, Haini; Chen, Dongping; Lu, Jiaqian; Jiao, Zheng; Chen, Bin; Zhang, Bin; Ye, Chaoyang; Liu, Li (Frontiers in Pharmacology, 2020)
Preclinical studies have shown that anti-cytokine therapies could alter drug dispositions through affecting cytochrome P450 synthesis; however, evidence and case reports evaluating clinical relevance of this interaction are scarce. This is the first reported case of interaction between cyclosporine and etanercept in a 42-year-old male patient with ankylosing spondylitis and immunoglobulin A nephropathy in whom cytokine levels were monitored both before and after cyclosporine initiation. The initiation of etanercept led to at least 2.5-folds increase in total clearance of cyclosporine. After comprehensive assessment and stepwise exclusion of alternative causes, it was considered that inflammation resolution with etanercept administration has highly induced clearance of cyclosporine, probably mediated by interleukin-2. The case has shown that co-administration of cyclosporine and anti-cytokine therapies such as etanercept needs close monitoring of trough levels. Physicians and pharmacists should be aware of similar interactions especially when the biological therapy is initiated or discontinued and for patients undergoing acute inflammation phase. Monitoring cytokine levels should be considered when drug-cytokine interaction is suspected.